2023
DOI: 10.1038/s41467-023-40322-w
|View full text |Cite
|
Sign up to set email alerts
|

spinDrop: a droplet microfluidic platform to maximise single-cell sequencing information content

Abstract: Droplet microfluidic methods have massively increased the throughput of single-cell sequencing campaigns. The benefit of scale-up is, however, accompanied by increased background noise when processing challenging samples and the overall RNA capture efficiency is lower. These drawbacks stem from the lack of strategies to enrich for high-quality material or specific cell types at the moment of cell encapsulation and the absence of implementable multi-step enzymatic processes that increase capture. Here we allevi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Being an open and flexible platform inDrops-2 can accommodate diverse workflows matching user-specific needs and has a potential to further democratize single cell technologies. Indeed, it has recently been shown that inDrops-based platforms such as VASA-Seq [35] outperforms commercial and plate-based methods in terms of gene and transcript capture, while spinDrops [73] benefits applications based on target cell enrichment by on-chip sorting. Beyond transcriptomics, inDrops-based platforms have been successfully tailored to probe other –omic modalities in individual cells such as open chromatin by HyDrop [33] or genome by Microbe-Seq [74], to name a few.…”
Section: Discussionmentioning
confidence: 99%
“…Being an open and flexible platform inDrops-2 can accommodate diverse workflows matching user-specific needs and has a potential to further democratize single cell technologies. Indeed, it has recently been shown that inDrops-based platforms such as VASA-Seq [35] outperforms commercial and plate-based methods in terms of gene and transcript capture, while spinDrops [73] benefits applications based on target cell enrichment by on-chip sorting. Beyond transcriptomics, inDrops-based platforms have been successfully tailored to probe other –omic modalities in individual cells such as open chromatin by HyDrop [33] or genome by Microbe-Seq [74], to name a few.…”
Section: Discussionmentioning
confidence: 99%
“…2d). 31 The first microfluidic device was utilized for the generation and sorting of droplets using in-line fluorescence-activated droplet sorting. The second microfluidic device was exploited for droplet pico-injection where RT mix can be injected into droplets after cell lysis.…”
Section: Ngs-based Scrna-seq Methodsmentioning
confidence: 99%
“…The single-cell screening can be further combined with genome sequencing to map the relationships between their genotypes and phenotypes. 191 Through sorting and sequencing of a specific set of IgG-secreting primary cells, the immunoglobulin G (IgG) secretion and the sequences of paired V H – V L genes can be coupled. 192 Single glial cells can also be sorted and collected by nucleic acid cytometry, thus enabling interrogation of the signaling pathways that regulate the pathogenic activities.…”
Section: Droplet-based Lab-on-a-chip Applications In Biotechnologymentioning
confidence: 99%